On certain classes of meromorphic harmonic concave functions defined by al-Oboudi operator - Khalid Challab,; Maslina Darus, (Pusat Pengajian Sains Matematik, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
In this work, a class of meromorphic harmonic concave functions defined by Oboudi operator in the punctured unit disc is introduced. Coefficient conditions, distortion inequalities, extreme points, convolution bounds, geometric convolution, integral convolution and convex combinations for functions f belonging to this class are obtained.